Search for New Astronomical Site in Indonesia : I. Global Atmospheric Parameters - Taufiq Hidayat; Putra Mahasena; Budi Dermawan (Institut Teknologi Bandung, 2010)
We present initial studies to search for the best possible sites for an astronomical observatory in Indonesia. Since the country occupies a vast geographical area, in so doing, we analyzed a number of basic atmospheric parameters based on GMS-NOAA meteorological satellite data at a low spatial resolution to identify some interesting feasible locations. The selected parameters are outgoing long wave radiation, temperature, precipitation, relative humidity, precipitable water, and wind profile, mostly available for a period of several decades. The data are averaged over 30 years to obtain a monthly average profile of Indonesian meteorological situation. The results suggest that regions of Nusa Tenggara Timur could offer promising sites and is merit to be explored further.Â